Unsur-unsur Kebudayaan sebagai faktor Integritas Masyarakat di Daerah Transmigrasi - Sutrisno, Slamet (Jurnal Filsafat "WISDOM", 1990)
Social integration is an important issue in Indonesia, because of its multi-racial characteristic. In the transmigration society, integration is principal issue due to its developing nature and because in it many individuals from various etchnic group live.